Women in the Korean Civil Service - Kim, Chon-Kyun (2003)
Are organizational characteristics, such as agency type, size, and growth, linked to female representation in the Korean civil service? This study analyzes the aggregate data regarding the female workforce in the Korean civil service in 2001 through multiple regression analysis. Findings indicate that the Korean women are likely to be underrepresented in most national agencies and severely underpresented at higher-level grades. While the Korean women doubled in the civil service for the last two decades, employment of women at the highest grade levels did not improve significantly. Redistributive agencies are directly linked to female representation in the Korean civil service regardless of grade levels, whereas agency size and growth are not related to female employment representation. To achieve gender equality and to expand female senior executive feed levels, the Korean government has provided the quotas for successful female applicants in the civil service entrance examinations at the lowest through middle level grades since 1996. The use of quotas and policies for gender equality could lead to changes in the entire public workforce, particularly fair representation at higher-level positions as well as the elimination of agency and occupational segregation. - Reproduced.
Keywords: Civil service - Korea; - Korea; Women in the civil service; Women in the civil service